Epigenetic demethylation of sFRPs, with emphasis on sFRP4 activation, leading to Wnt signalling suppression and histone modifications in breast, prostate, and ovary cancer stem cells. (April 2019) - Deshmukh, Abhijeet; Arfuso, Frank; Newsholme, Philip; Dharmarajan, Arun
Abstract: The expression and levels of secreted frizzled-related proteins (sFRPs), important Wnt signalling antagonists, have been reported to be reduced in various cancers, and are associated with disease progression and poor prognosis. During tumour development, all sFRP (1, 2, 3, 4, and 5) genes are hypermethylated, causing transcriptional silencing. sFRPs have an ability to sensitize tumour cells to chemotherapeutic drugs, enhancing cell death. Reduced Wnt signalling is associated with loss of cancer stem cell (CSC) viability. We investigated the possible involvement of methylation-mediated silencing of the sFRP gene family in CSCs derived from breast, prostate, and ovarian tumour cell lines. Real-time RT-PCR studies indicated that loss or downregulation of sFRP (1-5) expression in tumours is associated with promoter hypermethylation. Additionally, CSCs derived from all tumour cell lines with sFRP (1-5) promotor hypermethylation expressed sFRP (1-5) mRNA after treatment with 5-Azacytidine (5-Aza), especially sFRP4, implying that DNA methylation is the predominant epigenetic mechanism for sFRP (1-5) silencing. Furthermore, post-translational modification (PTM) in total and histone proteins was observed post 5-Aza and sFRP4 treatment. Protein levels of Wnt downstream signalling components (GSK3β, active β-catenin, and phospho β-catenin) and epigenetic factors of histones (acetyl histone H3, and H3K27me3) affecting PTM were analysed. Our findings suggest that downregulation of sFRP4 expression in endocrine-related cancers can be attributed to aberrant promoter hypermethylation in conjugation with histone modification, and indicate the important role of methylation-induced gene silencing of sFRP4 in survival and proliferation of CSCs derived from these cancers.